Changes in FIT values below the threshold of positivity and short-term risk of advanced colorectal neoplasia: Results from a population-based cancer screening program. (January 2019) - Buron, Andrea; Román, Marta; Augé, Josep M.; Macià, Francesc; Grau, Jaume; Sala, Maria; Louro, Javier; Martinez-Alonso, Montserrat; Alvarez-Urturi, Cristina; Andreu, Montserrat; Bessa, Xavier; Zaffalon, Diana; et al.
Abstract: Introduction: Increased values in the fecal immunochemical test (FIT) are correlated with increasingly severe colorectal neoplasia, but little attention has been given to FIT values below the cut-off point (negative FIT, nFIT). We analysed the relationship between the concentrations of two consecutive nFIT and the risk of following screen-detected advanced neoplasia and interval cancer (IC) in a population-based colorectal cancer screening program. Methods: FIT results were categorised into non-detectable nFIT (0–3.8 μg haemoglobin/g feces), low nFIT (3.9–9.9) and high nFIT (10.0–19.9). Multivariable adjusted logistic regression was used to estimate the odds ratios (OR) of advanced neoplasia and IC with the nFIT results in the first two screens. Results: More than 90% of the 42, 524 persons had non-detectable nFIT in the first and second screen; 4.5% and 5.8% had a low nFIT, respectively, and 2.2% and 2.9% had a high nFIT. The probability of testing positive and being diagnosed of advanced neoplasia or IC rose with increasing values of nFIT. Compared with those with two non-detectable nFIT results, the highest OR were found among those who had two high nFIT results (OR 21.75; 95% confidence interval: 12.44, 38.04) and those with one low nFIT and one high nFIT (ORs around 20). Conclusions: Participants with nFIT results above the detection limit of the test had an increased risk of advanced neoplasia and IC in subsequent participations. This information could be used in the design of personalised screening strategies. Highlights: Fecal haemoglobin (Hb) concentration below positivity threshold is strongly correlated with future risk of colorectal neoplasia. Two negative fecal immunochemical test (nFIT) between 10 and 19.9 μg Hb/g feces increase by 22 the risk of advanced neoplasia. Screenees with a 20-fold or higher increased risk of advanced neoplasia account for less than 1% of the uptakers with nFIT. Besides age and sex, quantitative values of nFIT should be included in the design of personalised screening strategies.